How perceived risk, benefit and trust determine user Fintech adoption: a new dimension for Islamic finance - Muhammad Ali; Syed Ali Raza; Bilal Khamis; Chin, Hong Puah; Hanudin Amin (Emerald Publishing Limited, 2021)
Purpose – This study’s objectives are twofold; first, this paper aims to explore the determinants of perceived benefit and perceived risk of Islamic Fintech. Second, this study examines the influence of perceived benefit, perceived risk and user trust on the intention to adopt Islamic Fintech. Design/methodology/approach – The sample of 350 was distributed among the respondents, while a usable sample of 321 was retained for the analysis. The study performed a self-administration survey to collect the sample data while the hypothesized model was tested using SmartPLS. Findings – The results revealed that perceived benefit and perceived risk were significant and positively influenced by their factors. Moreover, perceived benefits showed a positive and significant impact on trust. However, perceived risk had a negative and significant impact on trust. The results also found a strong positive and significant relationship between trust and intention to adopt Islamic Fintech. Originality/value – The outcome of this research may be used to develop strategies for Fintech and enables the financial sector to attain economies of scale in the world.